The linguistic representation of characters as readers in Pride and Prejudice - da Costa, Monica Chagas (BELT - Brazilian English Language Teaching Journal, 2012)
This paper intends to make an analysis of the language in the novel Pride and Prejudice, written by Jane Austen and first published in 1813. More specifically, I will analyse the language used to describe characters who are readers, through an enunciative perspective. It was based on the idea that every choice made by the author (enunciator) of a sentence is meaningful. Therefore, once we understand the choices the author makes when describing a reader, we are able to have a better understanding of what this author expects of his/her readers. In order to carry out the study, I read and selected the parts of Pride and Prejudice which are related to the descriptions of two characters (Elisabeth Bennet and Mr. Collins) as readers. Afterwards, this selection underwent a series of linguistic investigations, based on the enunciative theory developed by Émile Benveniste throughout his books Problemas de Linguística Geral I e II. These investigations enabled an understanding of how Jane Austen conveys her ideas concerning reading/readers linguistically speaking.